2012
DOI: 10.1166/jnn.2012.6574
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Zirconia (ZrO2) Nanoparticles and Zirconium Complexes

Abstract: The antimicrobial activities of zirconia (ZrO2) nanoparticles and zirconium mixed ligand complexes were studied on bacterial strains of E. coli, S. aureus and fungal strain of A. niger. The nanoparticles of zirconia and Zr(IV) complexes with different amino acids as ligands were synthesized by hydrothermal method. X-ray diffraction (XRD) and HRTEM confirmed the crystalline nature and morphology of the synthesized products. The antimicrobial studies revealed that the zirconia exhibits activity only against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(75 citation statements)
references
References 0 publications
3
72
0
Order By: Relevance
“…45,46 Additionally, it could be speculated that the nano-ZrO 2 has the same surface geometry, but with different shapes, different active facets may exhibit different antimicrobial activities. 29 Based on the results of the current study, significant differences were found between reinforced cold-cured acrylic resin and the control group. Moreover, significant differences were found between reinforced cold-cured acrylic resin as nano-ZrO 2 concentration increased, which confirmed the potential effect of nano-ZrO 2 in the prevention of Candida adhesion (Figure 3).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…45,46 Additionally, it could be speculated that the nano-ZrO 2 has the same surface geometry, but with different shapes, different active facets may exhibit different antimicrobial activities. 29 Based on the results of the current study, significant differences were found between reinforced cold-cured acrylic resin and the control group. Moreover, significant differences were found between reinforced cold-cured acrylic resin as nano-ZrO 2 concentration increased, which confirmed the potential effect of nano-ZrO 2 in the prevention of Candida adhesion (Figure 3).…”
Section: Discussionmentioning
confidence: 69%
“…This decrease in the colony number may be attributed to the antimicrobial activity of nano-ZrO 2 or its potential effect in improving surface properties. The antimicrobial effect of nano-ZrO 2 was reported by Jangra et al 29 who found that nano-ZrO 2 worked preliminarily on the bacterial strains of E. coli and S. aureus and on the fungal strain of A. niger and mainly showed activity against only E. coli. 36 Some studies showed that nano-ZrO 2 fills polymeric chain spaces and spaces on the surface, as its proper bonding to the polymer matrix resulted in smooth surfaces, which could prevent C. albicans adhesion.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…No evidence of toxic effects was observed [119,122]. ZrO2, acting on the bacterial strains of E. coli, S. aureus and fungal strain of A. niger, exhibited activity against only the E. coli [123]. There is no report that describes the toxicity of biogenically synthesized ZrO2 nanoparticles.…”
Section: Zirconia (Zro2) Nanoparticlesmentioning
confidence: 99%